Novelty Seeking, Harm Avoidance, and Cerebral Responses to Conflict Anticipation: An Exploratory Study - Hu, Jianping; Hu, Sien; Maisano, Julianna R.; Chao, Herta H.; Zhang, Sheng; Li, Chiang-Shan R. (Frontiers in Human Neuroscience, 2016)
Proactive control allows us to maneuver a changing environment and individuals are distinct in how they anticipate and approach such changes. Here, we examined how individual differences in personality traits influence cerebral responses to conflict anticipation, a critical process of proactive control. We explored this issue in an fMRI study of the stop signal task, in which the probability of stop signal – p(Stop) – was computed trial by trial with a Bayesian model. Higher p(Stop) is associated with prolonged go trial reaction time, indicating conflict anticipation and proactive control of motor response. Regional brain activations to conflict anticipation were correlated to novelty seeking (NS), harm avoidance (HA), reward dependence, as assessed by the Tridimensional Personality Questionnaire, with age and gender as covariates, in a whole-brain linear regression. Results showed that increased anticipation of the stop signal is associated with activations in the bilateral inferior parietal lobules (IPL), right lateral orbitofrontal cortex (lOFC), middle frontal gyrus (MFG), anterior pre-supplementary motor area (pre-SMA), and bilateral thalamus, with men showing greater activation in the IPL than women. NS correlated negatively to activity in the anterior pre-SMA, right IPL, and MFG/lOFC, and HA correlated negatively to activity in the thalamus during conflict anticipation. In addition, the negative association between NS and MFG/lOFC activity was significant in men but not in women. Thus, NS and HA traits are associated with reduced mobilization of cognitive control circuits when enhanced behavioral control is necessary. The findings from this exploratory study characterize the influence of NS and HA on proactive control and provide preliminary evidence for gender differences in these associations.